The Role Of School Principal Leadership In Improving Teacher Discipline - Ita Aristia Saida; Kurniawati, Naning; Wahyudhi, Sunu (International Journal of Education and Learning, 2025)
Teacher discipline is a crucial factor in supporting the quality of education in schools. However, in practice, there are still teachers who lack discipline in carrying out their duties, both in terms of attendance and professional responsibility. This study aims to describe the role of school principal leadership in improving teacher discipline at MTs Islahiyah Kalitidu. The research uses a qualitative approach with a case study method. Data were collected through interviews, observation, and documentation involving the principal and teachers. The results show that the principal plays a strategic role as a role model, rule enforcer, motivator, communicator, and evaluator. The strategies implemented include regular coaching, the application of rewards and punishments, personal approaches, and the development of a positive work culture. Supporting factors for leadership success include institutional support and open communication, while the inhibiting factors involve low individual awareness and heavy workloads. In conclusion, humanistic and adaptive leadership by the principal has proven effective in shaping sustainable teacher discipline